CMS Innovation Center Health Care Innovation Awards Evaluation Plan - Berry, Sandra H. (RAND Corporation, 2013)
The Center for Medicare and Medicaid Innovation has funded 108 projects implementing new service delivery or payment models that are intended to deliver lower cost through improving quality of care. This report describes a strategy for evaluating the results. Key dimensions include implementation effectiveness, program effectiveness, workforce issues, impact on priority populations, and context.